Are Size, Distance and Location Responsible for Species Richness in Home Garden Agroforestry Systems? - Subba, Mohit; Pala, Nazir A.; Shukla, Gopal; Chakarvarty, Sumit (Indian Forester, 2017)
The present study is a baseline survey of home gardens to explore the variation in species richness based on size, distance and location. The study site is terai zone in northern part of West Bengal covering three districts i, e. Jalpaiguri, part of Cooch Behar and Siliguri sub-division of Darjeeling district. A total of 100 home gardens were selected for the study. Among the sampled garden, 62 % were small (less than 0.5 ha), 26 % medium (0.5-1.0 ha) and only 12 % large (more than one ha). Similarly, 33%, 48% and 19 % of the total sampled gardens were located near, far and farthest from the main road of district or sub-division towns. A total of 55, 42 and 45 species were recorded from near, far and farthest category of home gardens, whereas 60, 38 and 44 number of species was recorded from small, medium and large home gardens, respectively.